PATOLOGI SOSIAL LINTAS GENERASI: KRISIS KEJUJURAN DAN RASIONALISASI KORUPSI DALAM CERPEN “CERITA CALON KORUPTOR” - Aa Hermawan; Halimah Halimah; Rudi Adi Nugroho; Yulianeta Yulianeta; Welsi Damayanti (Universitas Negeri Makassar, 2026)
This study analyzes the short story “Cerita Calon Koruptor” by Galang Gelar Taqwallah as a literary diagnosis of the social pathology of corruption in Indonesia. The study uses a qualitative descriptive method with a sociological literary approach. The primary data is the text of the short story “Cerita Calon Koruptor,” included in the anthology Merah pada Melati, while the secondary data consists of relevant literature. The analysis technique used is close reading across three stages: text reading, coding, and interpretation. This study found three main findings: corruption is depicted as an aspiration that is inherited and normalized across generations; the crisis of honesty is manifested through moral inversion and horizontal political brutality; and rationalization functions as a psychological mechanism that perpetuates the cycle of corruption. These findings underscore the importance of integrating the social pathology framework, which has been more widely used in sociological studies, into Indonesian literary studies as a more comprehensive analytical perspective compared to partial satirical or sociological approaches, and highlight the potential of short stories on corruption as teaching materials to build critical awareness of the normalization of corrupt values.